Rent Seeking, Capital Accumulation, and Macroeconomic Growth - Ben J. Heijdra; Pim Heijnen (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study the effects of time-using rent-seeking activities on the macroeconomic allocation and the economic growth rate. We formulate a highly stylized three-sector general equilibrium model with overlapping generations of individuals. The production side features one sector producing the capital good and two consumption goods sectors. All sectors operate under constant returns to scale technology with human and physical capital as inputs. One of the consumption goods sectors is a monopoly, where a continuum of agents compete for a share of monopoly profits. Agents are heterogeneous in their (intrinsically useless) rent-seeking ability. In the benchmark model each agent decides during youth on how much time to spend on lobbying activities, education, and production work. An intergenerational human capital externality of the 'shoulders of giants' type ensures that the model features endogenous growth. The rewards to rent-seeking accrue during youth and part of the additional income is saved. Interestingly, a move from a perfectly competitive economy to one involving monopolization and rent-seeking increases the steady-state economic growth rate in the benchmark model. We identify three main mechanisms affecting the growth rate under monopoly and rent-seeking, namely (a) the phase of life at which the rent-seeking booty is received (youth or old-age), (b) the kind of inputs used in the rent-seeking competition (raw time or education level), and (c) the type of growth engine (human or physical capital externality). The conclusions for the benchmark model are robust to changes in the mechanisms for (b) and (c) but not for (a). If rent-seeking rewards accrue during old-age then the move from a perfectly competitive economy to one involving monopolization and rent-seeking decreases the steady-state economic growth rate.
Keywords: D72; E24; L12; O41; O43; 330; rent seeking; economic growth; capital accumulation; monopolization; wasteful competition